The Effects of The Multiparty Regimes on Economic Growth and The Technological Changes - Plamadeala, Constantin (International Journal of Economics, Business, and Entrepreneurship, 2019)
The relationship between types of multiparty regimes and economic growth represents a disputed issue in nowadays. The aim of this essay is to examine the differences between multiparty authoritarian regimes and multiparty democratic regimes and their effects on sustainable economic growth and technological changes.